YPAR and Critical Epistemologies: Rethinking Education Research. Issue 1 (March 2017) - Caraballo, Limarys; Lozenski, Brian D.; Lyiscott, Jamila J.; Morrell, Ernest
Knowledges from academic and professional research-based institutions have long been valued over the organic intellectualism of those who are most affected by educational and social inequities. In contrast, participatory action research (PAR) projects are collective investigations that rely on indigenous knowledge, combined with the desire to take individual and/or collective action. PAR with youth (YPAR) engages in rigorous research inquiries and represents a radical effort in education research to value the inquiry-based knowledge production of the youth who directly experience the educational contexts that scholars endeavor to understand. In this chapter, we outline the foundations of YPAR and examine the distinct epistemological, methodological, and pedagogical contributions of an interdisciplinary corpus of YPAR studies and scholarship. We outline the origins and disciplines of YPAR and make a case for its role in education research, discuss its contributions to the field and the tensions and possibilities of YPAR across disciplines, and close by proposing a YPAR critical-epistemological framework that centers youth and their communities, alongside practitioners, scholars, and researchers, as knowledge producers and change agents for social justice.